Bishops in flight : exile and displacement in late antiquity - Barry, Jennifer, 1982- (University of California Press, 2019)
"Flight during times of persecution has a long and fraught history in early Christianity. In the third century, bishops who fled were considered cowards or, worse yet, heretics. On the face, flight meant denial of Christ and thus betrayal of faith and community. But by the fourth century, the terms of persecution changed as Christianity became the favored cult of the Roman Empire. Prominent Christians who fled and hence survived became founders and influencers of Christianity over time. Bishops in Flight examines the various ways these episcopal leaders both appealed to and altered the discourse of Christian flight to defend their status as purveyors of Christian truth, even when their exiles appeared to condemn them, illuminating how profoundly Christian authors deployed theological discourse and the rhetoric of heresy to respond to the phenomenal political instability of the fourth and fifth centuries"--Provided by publisher.